2022
DOI: 10.1101/2022.10.06.22280795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long COVID Risk and Pre-COVID Vaccination: An EHR-Based Cohort Study from the RECOVER Program

Abstract: Importance: Characterizing the effect of vaccination on long COVID allows for better healthcare recommendations. Objective: To determine if, and to what degree, vaccination prior to COVID-19 is associated with eventual long COVID onset, among those a documented COVID-19 infection. Design, Settings, and Participants: Retrospective cohort study of adults with evidence of COVID-19 between August 1, 2021 and January 31, 2022 based on electronic health records from eleven healthcare institutions taking part in th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 28 publications
(40 reference statements)
1
28
1
Order By: Relevance
“…Among participants with a first infection during the Omicron era, PASC frequency was higher among those with recurrent infections, corroborating electronic health record–based studies . Though studies on the effect of vaccination are conflicting, these findings of modest reduction in PASC frequency among fully vaccinated participants align with recent systematic reviews …”
Section: Discussionsupporting
confidence: 72%
“…Among participants with a first infection during the Omicron era, PASC frequency was higher among those with recurrent infections, corroborating electronic health record–based studies . Though studies on the effect of vaccination are conflicting, these findings of modest reduction in PASC frequency among fully vaccinated participants align with recent systematic reviews …”
Section: Discussionsupporting
confidence: 72%
“…Several studies have described a protective association between SARS-CoV-2 vaccination and long COVID symptoms [17,40] and this protection seems to persist also in breakthrough infections [41]. We have not found any effect of vaccination about the risk of long COVID at 3 months onset in any of the adjusted logistic models (any symptoms, neurobehavioral symptoms).…”
Section: Discussioncontrasting
confidence: 46%
“…19,20,21,22 Gompertzian Analysis has found that unlike Gompertzian Lethality, Long COVID occurs at relatively equivalent rates across ages (APPENDIX-FIGURE 40). 23,24 Vaccination has been found to protect against Long COVID , (APPENDIX-FIGURE 41), 25,2627,28 with protection increasing with each additional dose, 29 although the data so are far not sufficient to determine which symptoms are prevented, and most importantly, to what degree pandemic associated excess mortality is reduced, if at all, but vaccination. 30,31 Clearly, this remains a problem of high importance, which should be decipherable by Gompertzian Analysis .…”
Section: Resultsmentioning
confidence: 99%